Investigating the Effect of School Principals’ Creative Leadership Behaviors on Teachers’ Innovative Work Behavior (Journal of Management and Educational Sciences, 2025)
This study aims to examine the effects of school principals' creative leadership behaviors on teachers' innovative work behavior. The study was conducted using a relational screening model. As a result of the study, it is seen that teachers' innovative work behavior and school principals' creative leadership traits perceptions are above average. In the examination according to gender; men's perception of innovative work behavior is higher than women. Again, men's perception of school principals' creative leadership traits is higher than women. In the examination according to age; teachers aged 41 and above have higher perceptions of school principals' creative leadership traits than teachers aged 31-40. On the other hand, the remaining innovative work behavior perceptions do not change according to age groups. In the examination according to previous innovation training status; no difference was found between those who received innovation training and those who did not. In the examination according to years of service; the creative leadership perception of school principals of teachers with 16 years of service and above was higher than teachers with 6-10 years of service and 11-15 years of service. Finally, a moderate, significant and positive relationship was found between participants' perceptions of innovative work behavior and school principals' creative leadership traits. Again, the creative leadership characteristics of school principals significantly predict teachers' perceptions of innovative work behavior. In other words, a 100-unit increase in the dimension of the creative leadership characteristics of school principals increases innovative work behavior by 44.6%.